2006
DOI: 10.1016/j.theriogenology.2005.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods for obtaining spermatozoa from the cauda epididymis of Iberian red deer

Abstract: We have compared two methods for salvaging epididymal sperm from post-mortem samples from Iberian red deer. Of each pair of testicles (29 samples), one cauda epididymis was processed by means of cuts (sperm was immediately diluted with extender) and the other was detached from the corpus and flushed from the vas deferens with 1 mL of extender. Sperm was processed for cryopreservation, and analyzed just after recovery, pre-freezing and post-thawing. Total spermatozoa recovered, contamination (concentration of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 34 publications
1
63
0
10
Order By: Relevance
“…Based on our results we hypotheses that ovine epididymal spermatozoa exposed to ambient temperature could yield good fertility up to 24 hours post mortem, however efforts should be focused on preservation (refrigeration or cryopreservation) of epididymal spermatozoa as soon as possible. -Pastor et al (2006) compared a slicing method with retrograde flushing for recovery of red deer spermatozoa, these authors found no difference between the methods in sperm recovery and motility immediately after collection but identified better motility, acrosome integrity and viability in sperm collected by retrograde flushing when spermatozoa were diluted and cooled for two hours. In our preliminary work, we identified limitations of the retrograde flushing method on ram cauda epididymis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our results we hypotheses that ovine epididymal spermatozoa exposed to ambient temperature could yield good fertility up to 24 hours post mortem, however efforts should be focused on preservation (refrigeration or cryopreservation) of epididymal spermatozoa as soon as possible. -Pastor et al (2006) compared a slicing method with retrograde flushing for recovery of red deer spermatozoa, these authors found no difference between the methods in sperm recovery and motility immediately after collection but identified better motility, acrosome integrity and viability in sperm collected by retrograde flushing when spermatozoa were diluted and cooled for two hours. In our preliminary work, we identified limitations of the retrograde flushing method on ram cauda epididymis.…”
Section: Discussionmentioning
confidence: 99%
“…Petri plates were angled so that the extender washed the spermatozoa to accumulate at one end of the plate. After five minutes a pipette was used to collect the diluted spermatozoa from the Petri dish and the sample was placed in a conical tube (Falcon BD) (Martinez-Pastor et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays concrete examples of application of post-mortem sperm recovery from the epididymis are available for conservation of endangered species [37] and in constructing semen banks [38][39][40]. Preservation of epididymal sperm from accidental dead or slaughtered animals has been reported in several domestic and wild species as boar [41], cattle [42,43], goat [44], ibex [45,46], red deer [47] and sheep [38,48]. However epididymal sperm extraction sometimes is not easily practicable in marginal areas, due to the lack of facilities and expertise near the farming areas of local breeds.…”
Section: Ex Situ Conservation Strategiesmentioning
confidence: 99%
“…Sperm collected from caudae epididymides has been used in reproductive techniques developed for several species, including the mouse , dog (Yu and Leibo, 2002;Garcia-Macias et al, 2006a), deer (Hishinuma et al, 2003;Martinez-Pastor et al, 2006), pig (Kikuchi et al, 1998), ram (Kaabi et al, 2003), bull (Foote, 2000), horse (Vieira et al, 2012), bison (Krishnakumar et al, 2011), bear (Garcia-Macias et al, 2006b) and even humans (McLachlan, 1998). The sampling of epididymal spermatozoa has been reported after mincing or cutting the epididymal tubule and collecting the exudate directly (Martins et al, 2009;Tamayo-Canul et al, 2011b) or diluting in a medium solution (Hori et al, 2005b;Ehling et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The sampling of epididymal spermatozoa has been reported after mincing or cutting the epididymal tubule and collecting the exudate directly (Martins et al, 2009;Tamayo-Canul et al, 2011b) or diluting in a medium solution (Hori et al, 2005b;Ehling et al, 2006). To avoid any blood contamination and to obtain a maximum number of spermatozoa, epididymal sampling has also been performed by retroflushing the epididymal lumen content from the deferent duct with air (Kikuchi et al, 1998;Vieira et al, 2012), with physiological solution (Dacheux, 1980;Martinez-Pastor et al, 2006), sodium citrate-egg yolk or paraffin oil (Dacheux et al, 2006). Although some differences have been reported between caudal and ejaculated sperm (GarciaMacias et al, 2006a), the fertility of epididymal sperm used either fresh or frozen-thawed for insemination has been found to be similar to ejaculated samples (Ehling et al, 2006;Varisli et al, 2009;Alvarez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%